Tetrandrine antagonizes acute megakaryoblastic leukaemia growth by forcing autophagy‐mediated differentiation. (2nd November 2017) - Liu, Ting; Zhang, Zhenxing; Yu, Chunjie; Zeng, Chang; Xu, Xiaoqing; Wu, Guixian; Huang, Zan; Li, Wenhua
Abstract : Background and Purpose: The poor prognosis of acute megakaryoblastic leukaemia (AMKL) means there is a need to develop novel therapeutic methods to treat this condition. It was recently shown that inducing megakaryoblasts to undergo terminal differentiation is effective as a treatment for AMKL. This encouraged us to identify a compound that induces megakaryocyte differentiation, which could then act as a potent anti‐leukaemia agent. Experimental Approach: The effects of tetrandrine on the expression of CD41 and cell morphology were investigated in AMKL cells. We used CRISPR/Cas9 knockout system to knock out ATG7 and verify the role of autophagy in tetrandrine‐induced megakaryocyte differentiation. shNotch1 and CA‐Akt were transfected into K562 cells to examine the downstream pathways of ROS signalling and the mechanistic basis of the tetrandrine‐induced megakaryocyte differentiation. The anti‐leukaemia effects of tetrandrine were analysed both in vitro and in vivo . Key Results: A low dose of tetrandrine induced cell cycle arrest and megakaryocyte differentiation in AMKL cells via activation of autophagy. Molecularly, we demonstrated that this effect is mediated by activation of Notch1 and Akt and subsequent accumulation of ROS. In contrast, in normal mouse fetal liver cells, although tetrandrine induced autophagy, it did not affect cell proliferation or promote megakaryocyte differentiation, suggesting a specific effect of tetrandrine in malignant megakaryoblasts. Finally, tetrandrine also showed in vivo efficacy in an AMKL xenograft mouse model. Conclusions and Implications: Modulating autophagy‐mediated differentiation may be a novel strategy for treating AMKL, and tetrandrine has the potential to be developed as a differentiation‐inducing agent for AMKL chemotherapy.